2022
DOI: 10.1002/aelm.202201007
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Stacked Dual‐Channel Transistors with High Electron Mobility Using a Planar Heterojunction Architecture

Abstract: Thin‐film transistors based on metal oxide semiconductors have become a mainstream technology for application in driving low‐cost backplanes of active matrix liquid crystal displays. Although significant progress has been made in traditional marketable devices based on physical vapor deposition derived metal oxides, it has still been hindered by low yield and poor compatibility. Fortunately, developing solution‐based 1D nanofiber networks to act as the fundamental building blocks for transistor has proven to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
1
0
Order By: Relevance
“…In our previous investigation, we have demonstrated that network modes stacked by In 2 O 3 and ZnO NWs allow the formation of a 2DEG localized at the contact point, providing a gain for electron transport. [ 21 ] Assuming that the two layers of materials in the coaxial structure are bounded in specific regions, and the electrons on the ZnO layer are expected to migrate toward In 2 O 3 and fall into the potential well due to the remapping of the conduction band. Figure S4 (Supporting Information) depicts the energy band diagram of the In 2 O 3 /ZnO heterojunction (HJ) interface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous investigation, we have demonstrated that network modes stacked by In 2 O 3 and ZnO NWs allow the formation of a 2DEG localized at the contact point, providing a gain for electron transport. [ 21 ] Assuming that the two layers of materials in the coaxial structure are bounded in specific regions, and the electrons on the ZnO layer are expected to migrate toward In 2 O 3 and fall into the potential well due to the remapping of the conduction band. Figure S4 (Supporting Information) depicts the energy band diagram of the In 2 O 3 /ZnO heterojunction (HJ) interface.…”
Section: Resultsmentioning
confidence: 99%
“…For constructing devices on Al 2 O 3 gate insulating layers the process was consistent with the above and a detailed procedure for the preparation of Al 2 O 3 by atomic layer deposition (ALD) can be found on the previous work. [21] NWs Characterization: The morphology and orientation distribution of NWs were observed using optical microscopy and SEM (REGULUS 8230). The microstructure, elemental components, and crystal phase composition of NWs were examined by XRD (SmartLab 9 kW) and TEM (JEM-2100).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 ] Recently, the buzz about 1D MOS nanofibers (NFs) or NWs as active materials for FETs has also continued. [ 8–12 ] For instance, Wang et al. successfully demonstrated the integration of IGZO‐based NFNs in multifunctional flexible stretchable electronic FETs, confirming the potential value of inorganic 1D IGZO NFs in electronic devices.…”
Section: Introductionmentioning
confidence: 94%